Linezolid and Rifampicin Combination to Combat cfr-Positive Multidrug-Resistant MRSA in Murine Models of Bacteremia and Skin and Skin Structure Infection - Zhou, Yu-Feng; Li, Liang; Tao, Meng-Ting; Sun, Jian; Liao, Xiao-Ping; Liu, Ya-Hong; Xiong, Yan Q. (Frontiers in Microbiology, 2020)
Linezolid resistance mediated by the cfr gene in MRSA represents a global concern. We investigated relevant phenotype differences between cfr-positive and -negative MRSA that contribute to pathogenesis, and the efficacy of linezolid-based combination therapies in murine models of bacteremia and skin and skin structure infection (SSSI). As a group, cfr-positive MRSA exhibited significantly reduced susceptibilities to the host defense peptides tPMPs, hNP-1 and LL-37 (P<0.01). In addition, increased binding to fibronectin and endothelial cells paralleled robust biofilm formation in cfr-positive vs. -negative MRSA. In vitro phenotypes of cfr-positive MRSA translated into poor outcomes of linezolid monotherapy in vivo in murine bacteremia and SSSI models. Importantly, rifampicin showed synergistic activity as a combinatorial partner with linezolid, and the EC50 of linezolid decreased 6-fold in the presence of rifampicin. Furthermore, this combination therapy displayed efficacy against cfr-positive MRSA at clinically relevant doses. Altogether, these data suggest that the use of linezolid in combination with rifampicin poses a viable therapeutic alternative for bacteremia and SSSI caused by cfr-positive multidrug resistant MRSA.